Redetermination of dysprosium trinickel from single-crystal X-ray data - Levytskyy, Volodymyr (International Union of Crystallography, 2012)
The crystal structure of the title compound, DyNi(3), was redetermined from single-crystal X-ray diffraction data. In comparison with previous studies based on powder X-ray diffraction data [Lemaire & Paccard (1969 ▶). Bull. Soc. Fr. Minéral. Cristallogr. 92, 9–16; Tsai et al. (1974 ▶). J. Appl. Phys. 45, 3582–3586], the present redetermination revealed refined coordinates and anisotropic displacement parameters for all atoms. The crystal structure of DyNi(3) adopts the PuNi(3) structure type and can be derived from the CaCu(5) structure type as an intergrowth structure. The asymmetric unit contains two Dy sites (site symmetries 3m and -3) and three Ni sites (m, 3m and -3m). The two different coordination polyhedra of Dy are a Frank–Kasper polyhedron formed by four Dy and 12 Ni atoms and a pseudo-Frank–Kasper polyhedron formed by two Dy and 18 Ni atoms. The three different coordination polyhedra of Ni are Frank–Kasper icosahedra formed by five Dy and seven Ni atoms, three Dy and nine Ni atoms, and six Dy and six Ni atoms.